1999
DOI: 10.1021/jf970967v
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Different Bean Varieties (Phaseolus vulgaris) of Northwestern Argentina (Region NOA):  Cultivation Zone Influence

Abstract: There have been prior investigations concerning the environmental effects and especially soil conditions upon the proximate analysis and mineral content of grains. However, the studies are not complete and have not involved beans grown in the northwestern regions of Argentina. For this reason, this study was initiated to determine the concentration of protein, moisture, ash, fat, and minerals of various bean samples grown in northwestern Argentina. Six varieties of beans were taken from seven different regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
15

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 0 publications
1
10
0
15
Order By: Relevance
“…This complex modifies the product texture, rheological properties, digestibility and storage stability (Kaur and Singh 2000). The ash content for the samples analyzed in this work (3.62 %) was similar to that reported elsewhere for different varieties of Argentinean black beans (Sammán et al 1999). Hence, the black bean flour, obtained from the Negro Queretaro variety used in this study constitutes a healthy food product, that combined with cereals like maize (Zea mays), rich in sulfur amino acids, may produce a nutritional food with a good energy balance (Pachón et al 2009).…”
Section: Proximate Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…This complex modifies the product texture, rheological properties, digestibility and storage stability (Kaur and Singh 2000). The ash content for the samples analyzed in this work (3.62 %) was similar to that reported elsewhere for different varieties of Argentinean black beans (Sammán et al 1999). Hence, the black bean flour, obtained from the Negro Queretaro variety used in this study constitutes a healthy food product, that combined with cereals like maize (Zea mays), rich in sulfur amino acids, may produce a nutritional food with a good energy balance (Pachón et al 2009).…”
Section: Proximate Analysissupporting
confidence: 85%
“…The moisture content of "negro Querétaro" beans was similar (8.35 %) to that found for four varieties of Negro beans (8.87-9.19 %) (CarmonaGarcía et al 2007). Sammán et al (1999) found that the moisture content of Argentinean black beans ranged from 11.78 to 13.37 %. (2004) reported values of 1.26 to 2.8 %, for different black bean varieties.…”
Section: Proximate Analysismentioning
confidence: 99%
“…ANDRADE et al [1,2,3], analisando os teores de cobre em frutas, cereais e hortaliças do tipo C, encontrou em média respectivamente os seguintes valores: 0,13mg%, 0,21mg% e 0,24mg%. Estudos mostram que o teor de cobre encontrado em variedades de feijões, espécies Phaseolus vulgaris e Mucuna pruriens, foi de 0,8 a 2,2mg% [14,17]. Comparando estes grupos de alimentos com as leguminosas, pode-se considerar que estas são fontes de cobre.…”
Section: -Resultados E Discussãounclassified
“…Em cereais, frutas e hortaliças do tipo C este mineral se encontra em média, respectivamente, 1,55mg%, 0,18mg% e 0,33mg% [1,2,3,14,17]. Observa-se que o teor de zinco nas leguminosas é superior a 10 vezes o valor encontrado nas frutas e hortaliças do tipo C. O processamento tér-mico tanto em meio aquoso quanto em meio salino não promoveu perda significativa deste metal para a maioria das amostras analisadas.…”
Section: -Resultados E Discussãounclassified
“…O ácido ascórbico, como agente redutor, mantém o ferro dos alimentos no estado ferroso, que é mais solúvel. Também, forma quelato ferro-ascorbato, que se mantém solúvel mesmo com o aumento do pH no intestino delgado proximal [25]. O ferro da alimentação contido nas frutas e vegetais, que são ricos em ácido ascórbico, normalmente, é 15% disponível.…”
Section: -Introduçãounclassified